2002
DOI: 10.2320/matertrans.43.2173
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Mechanism of Copper at 623-1073 K

Abstract: In reviewing the results reported for copper oxidation at intermediate temperatures from 573 to 1173 K, the oxidation mechanism at the lower part of this temperature range and the reason for the change in activation energy with decreasing the temperature remain unclear. To make it clear, copper oxidation is studied at 623-1073 K under 0.1 MPa O 2 using a commercial 99.9999% pure copper. The oxidation kinetics is essentially parabolic, and the activation energy decreases from 111 kJ/mol at 873-1073 K to 40 kJ/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 10 publications
9
94
0
1
Order By: Relevance
“…Park and Natesan [4] suggested that the decreased oxidation activation energy for pure Cu oxidized at 773-973 K is attributed to the increasing grain boundary diffusion. However, Zhu et al [10] have studied the oxidation behaviors of 4N (99.99 wt.%) Cu at 623-773 K and considered that the higher oxidation activation energy value is due to the impurity segregation or agglomeration at the grain boundary hindering the grain boundary diffusion. In light of the latter case, our results can be understood.…”
Section: Oxidation Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Park and Natesan [4] suggested that the decreased oxidation activation energy for pure Cu oxidized at 773-973 K is attributed to the increasing grain boundary diffusion. However, Zhu et al [10] have studied the oxidation behaviors of 4N (99.99 wt.%) Cu at 623-773 K and considered that the higher oxidation activation energy value is due to the impurity segregation or agglomeration at the grain boundary hindering the grain boundary diffusion. In light of the latter case, our results can be understood.…”
Section: Oxidation Kineticsmentioning
confidence: 99%
“…Recent papers [4][5][6][7][8][9][10] revealed that the oxidation activation energies of Cu were very different as reviewed in Table 1. As can be seen that the value of oxidation activation energy at 623-823 K for OFHC Cu [7] is 84 kJ/mol, which is higher than that of 52 kJ/mol for a 2N Cu [9] and 40 kJ/mol for a floating zone refined Cu [9][10] a 6N Cu [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of Cu involves two phases: partial oxidation forms Cu 2 O (red) and total oxidation produces CuO (black). 10 The formation of these two oxides is likely accompanied by the formation of mixed oxides including Mo and Tc, which would interfere with the formation of Tc 2 O 7 and, thus, confound the separation process, which is optimized to condense Tc 2 O 7 in the cooler regions of the QT. Figure 7 shows the state of the copper support after reaction with oxygen at elevated temperature.…”
Section: Chemical Processingmentioning
confidence: 99%
“…1,2) However, there are some problems in fabrication process, for example, surface oxidation of copper. 3,4) Furthermore, copper base alloys are used for electrical parts such as lead frame and connector, and surface stabilization of them is required for applying them to microelectronics. Several studies on oxidation of Cu alloys have been performed, and Al, Ti and Cr have been reported to be useful as alloying elements for improving the oxidation resistance of copper.…”
Section: Introductionmentioning
confidence: 99%